Earthquake-induced risk assessment of cultural heritage based on InSAR and seismic intensity: A case study of Zhalang temple affected by the 2021 Mw 7.4 Maduo (China) earthquake. (January 2023) - Zhu, Meng; Chen, Fulong; Fu, Bihong; Chen, Wenkai; Qiao, Yunfei; Shi, Pilong; Zhou, Wei; Lin, Hui; Liao, Ya'ao; Gao, Sheng
Abstract: Earthquakes have been acknowledged as threats to heritages for a long time in the past decades. Many scientific publications and international guidelines have addressed this issue. However, the related reports are still lacking particularly for the 2021 Mw 7.4 Maduo earthquake and its surrounding heritage sites, even though this event was the largest earthquake in China after 2008 with 13 National Key Protected Cultural Relic Units (NKPCRUs) of China located in the surrounding areas within 200 km from the epicenter. On May 21, 2021, an Mw 7.4 earthquake struck Maduo County in Qinghai Province, China. The earthquake was large in magnitude and caused ∼150 km of surface rupture. The integrity and authenticity of cultural heritages near the epicenter are under severe threat, making it critically important to quantify the potential damages and vulnerability of these sites affected by the Mw 7.4 earthquake. Nevertheless, many geological and geophysical studies related to this earthquake have been conducted, but none of them consider the seismic damage to the heritage sites. To fulfill this gap, the Zhalang temple (also known as "Golok Peaceful Liberation Memorial") which was a Tibetan Buddhist monastery located ∼140 km away from the Mw 7.4 epicenter of the 2021 Maduo earthquake was taken as an example to investigate whether and how the strong earthquake could affect a cultural heritage in such a distance. Collaborative monitoring based on InSAR and seismic intensity was conducted to measure the earthquake-induced deformation and characterize the risks and damages to cultural heritages by earthquakes. First, fast responses within 30 min based on the seismic method were performed. The PGV-vS30 intensity, that was the peak ground velocities (PGV) further site-corrected by the site conditions of the time-averaged shear-wave velocity to 30 m depth (vS30 ) seismic intensity map was obtained, which provided a general and fast guidance to preliminary determinations of the severe disaster area and the scope of the disaster area. Initial decisions could be made about whether or where a certain location should be taken into further on-site inspection. Then, the Interferometric Synthetic Aperture Radar (InSAR) processing of Sentinel-1 images was performed to define two-dimensional (2D) East-West (E-W) and vertical co-seismic deformation maps near the Zhalang temple. Finally, the measurements obtained by seismic and InSAR methods were validated by unmanned aerial vehicle (UAV) imagery and field surveying. The results showed that: the maximum E-W striking deformation was ∼2.54 cm toward the east and the vertical subsidence was ∼0.01 cm centered on the Zhalang temple, suggesting that the E-W striking deformation significantly affected the surrounding region. Moreover, the spatial heterogeneity indicator of the InSAR deformation maps revealed the locations of underground faults with surface expressions. Further field survey detected surface fractures at Zhalang temple due to secondary effects of the Mw 7.4 earthquake. The genetic process of faulting and fracturing is crucial in terms of hazard assessment and mitigation strategies. In countries with strong environmental and seismic risks, the presented work contributes to the disaster risk reduction (DRR) of heritages in natural-hazard-prone areas and also takes on a social value because it provided supplements for the protection of a heritage that represents the very identity nationwide. Graphical abstract: Image 1